2015
DOI: 10.1111/jopr.12302
|View full text |Cite
|
Sign up to set email alerts
|

Fabricating Complete Dentures with CAD/CAM and RP Technologies

Abstract: Two techological approaches for fabricating dentures; computer-aided design and computer-aided manufacturing (CAD/CAM) and rapid prototyping (RP), are combined with the conventional techniques of impression and jaw relation recording to determine their feasibility and applicability. Maxillary and mandibular edentulous jaw models were produced using silicone molds. After obtaining a gypsum working model, acrylic bases were crafted, and occlusal rims for each model were fabricated with previously determined stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
62
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(67 citation statements)
references
References 10 publications
0
62
0
1
Order By: Relevance
“…In 2015, Bilgin et al described a combination of conventional and digital procedures where the DLP AM technology was used to fabricate the denture teeth in one piece with a micro‐hybrid nano‐filled resin. Similar to previous authors, the digitalization of the working edentulous plaster casts mounted on the articulator and the wax rims was obtained using a laboratory dental scanner.…”
Section: Prosthodontic Applicationsmentioning
confidence: 99%
“…In 2015, Bilgin et al described a combination of conventional and digital procedures where the DLP AM technology was used to fabricate the denture teeth in one piece with a micro‐hybrid nano‐filled resin. Similar to previous authors, the digitalization of the working edentulous plaster casts mounted on the articulator and the wax rims was obtained using a laboratory dental scanner.…”
Section: Prosthodontic Applicationsmentioning
confidence: 99%
“…Such technology offers numerous advantages, most importantly is the reduced chair time required for treatment as it replaces the clinical step of impression taking and all steps required for the setting of the artificial teeth with the advantage of patients’ participation in denture design. Additionally, it has been suggested that the one-set alignment of the artificial teeth could increase the denture durability (24). Others have reported that CAD CAM technology can improve the accuracy of denture fit since the utilization of pre-polymerized acrylic resin eradicates the shrinkage issues related to the use of the heat cured acrylic resin base.…”
Section: Introductionmentioning
confidence: 99%
“…Fernandez et al found that over half of all prosthodontic program directors who responded to a survey have incorporated CAD/CAM dentures into their curriculum. In addition, other companies have developed their own CAD/CAM denture technology . Two prospective studies have evaluated patient outcomes in vivo, including fit (retention) .…”
mentioning
confidence: 99%